The Role of Attitude in The Relationship of Convenience and Customer Service to Purchase Intention on the PT Farah Oriental Carpet Website - Benazir Fahim; Helena Sidartha (International Journal of Review Management Business and Entrepreneurship (RMBE), 2023)
This study aims to determine the role of attitude as an intervening variable in the relationship between convenience and customer service towards purchase intention on the PT Farah Oriental Carpet website. The population in this study are the customers of PT Farah Oriental Carpet. For the sampling, this study applied a purposive sampling method with the fulfillment of the criteria which includes having an interest in the products or services offered by PT Farah Oriental Carpet, being part of PT Farah Oriental Carpet's customers who received Farah's Oriental Rugs &; Carpet's WhatsApp Blast Website, and having visited Farah's Oriental Rugs &; Carpet's Website page. Therefore, 140 samples were collected in this study using the Hair formula. The data analysis method used is quantitative and processed using SmartPLS 3.0 software. The results of this study indicate that convenience and customer service have a significant effect on attitude, convenience and customer service have a significant effect on purchase intention, and attitude have a significant effect on purchase intention.